SISTEMA INFORMÁTICO PARA EL COBRO DE LOS PERMISOS DEL CUERPO DE BOMBEROS DEL CANTÓN BABA. - Cerezo Esmeralda, David Javier (2018)
The present investigation has to do with the elaboration and development of a computer system, for the collection of the permits of the fire department of the Baba Canton. This system will handle information about documents and important data where they are involved, software, hardware and the personnel that will manipulate it. The reason why the software solution will be developed is as follows; lack of control of information, prevention of falsification of permits, incorrect data, loss of time and waste of resources. The purpose of solving the problem is for the staff that manipulates this type of documentation, have timely information, ease of management of the process, agility and speed when presenting a report and also encourage more processes to be automated and be on par with how technology is developed in these times. The present project is divided into three chapters. Chapter number one: the diagnosis of needs and requirements will be developed, it will also be detailed in the area where it will influence and execute the prototype, relevant aspects, the reason why the prototype will be made, the requirements; what is needed to be able to carry out the computer solution. In chapter number two: the development of the prototype is detailed; it is defined in what language it is going to develop and what functions it is going to do. It also shows the theory that supports the realization of the prototype, the objectives, the design of the prototype, details that show the execution and assembly of the prototype.